Centralized Collective Bargaining : U.S.-Canada Experience - Downie, Bryan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
The author is concerned with bi-national bargaining which entails the delegation of decision-making power from Canada to the United States either through adherence to a U.S. pattern or standard and/or through the actual delegation of decision-making power in collective bargaining to U.S. officials. This paper attempts to take an initial step in the direction of increasing our understanding of what generates bi-national arrangements, what tactics and strategies are involved, and the implications.